Biologics for Non-Cancer Dermatological Diseases: Analysis on China’s Clinical Trial Registration Trend From 2016 to 2020 - Zhu, Beibei; Liu, Yi; Li, Jing; Ni, Qi; Yin, Zheng; Zhu, Junli; Chen, Ken; Yang, Xueyuan (Frontiers in Pharmacology, 2022)
Background: In the past 5 years, China has quickly followed US’s steps to approve the new drug application of biologics for dermatological diseases. There is an increasing interest in the current biologics landscape as well as further potentials in China. Our study aims to analyze features of clinical trials on non-cancer dermatological biologics, synthesize recent achievements and impediments, in order to forecast the development trends in China. Methods: Three registers (Chinese Clinical Trial Registry, Center for Drug Evaluation and ClinicalTrials.gov) were searched for clinical trials of non-cancer dermatological biologics initiated between 2016 and 2020 in mainland China. Trials information (first posted year, sponsor type, study phase and site, recruitment status, disease, drug target, and drug registration type), and certain study design (selection of control group, primary efficacy outcome, and inclusion of patient-reported outcome, for non-phase I or II trials only) information were extracted and analyzed. Results: A total of 60 trials were identified. The number of registered dermatological biologic trials significantly increased with an annual increase of 59% from 2016 to 2020, primarily driven by psoriasis (47/60, 78.3%) and atopic dermatitis (6/60, 10.0%) trials. The tumor necrosis factor (TNF)-α and interleukin (IL)-17 remained the hottest drug targets (17/60, 28.3% for TNF-α and 18/60, 30.0% for IL-17). Besides TNF-α and IL-17, many new psoriasis drug targets came into place since 2018 (IL-12/23) and 2019 (IL-36 and glucagon-like peptide-1 (GLP-1)). Thirty percent (18/60) of the trials were conducted for biosimilar products, all of which were sponsored by local pharmaceutical companies, and 88.9% of which were targeting on TNF-α. Target of IL-36, IL-5 and IgE were only available in trials sponsored by global companies. Conclusion: There was a great progress on the innovation of dermatological biologics in the past 5 years in China in terms of surged number of clinical trials, increased biosimilars and “me-too” drugs which greatly improved patient access to novel treatments, execution of parallel clinical trials, and improved hospital GCP office and regulatory environment. Further efforts for local pharmaceutical companies should include relocating resources to exploring novel drug targets and dermatological diseases other than psoriasis or atopic dermatitis.